Innovation in the local administration system in Egypt - Abdulrahman, Mustafa Adel (AUC Knowledge Fountain, 2016)
The Egyptian public sector always described as a highly centralized system, with an inflexible hierarchical structure and high levels of formal relationships channeling its communications through public enterprises and institutions. Even establishing the local administration system as an approach of decentralization, it still highly connected and governed by the central government. On the other hand, innovation in public sector studies and application in last two decades gained much interest from scholars, practitioners and even leaders and policy makers as an approach to enhance public sector efficiency and effectiveness. Accordingly, this study aims to explore innovation in the public sector in Egypt, evaluating the extent to which it permits innovation. In addition, it aims to analyze experiences of innovation, if any, within the public sector in Egypt, discussing them in relation to the latest advances in academic understandings of innovation. The local administration system has been selected as a model to be examined in this study as it can represent the public sector in Egypt on a larger scale, as it is a core part of this sector. The study evaluates the laws, structures, and dynamics that constitute the framework of the local administration system. Furthermore, it explores the main constraints on innovation within the system. To develop and support the argument, which emerges from the literature review, this study employs qualitative research methods, namely interviews, as a method to collect data from various informants working in and/or with the public sector. The study draws the broad conclusion that the current laws, structures, and dynamics of the public sector in Egypt discourage innovation. However, the study also uncovers evidence of innovation in the public sector, of a type in harmony with recent advances in contemporary academic understandings of innovation. In addition, the study found the existence of different types of innovative applications like product, service, and process occurred more frequently than other categories of innovation, such as organizational and strategic innovation. It also found that leadership plays an effective role within the public administration system in Egypt. These examples of innovation flourished only when they were applied in parallel with, not within, the current laws, structures, and dynamics of the local administration system in the public sector. Nevertheless, poorly skilled staff with low wages, the absence of a competitive spirit, a lack of positive culture and bad working conditions, along with rigid centrality and apathy all constitute real barriers to the flourishing and dissemination of innovation within Egypt’s public sector.